High tunable dielectric response of Pb0.87Ba0.1La0.02 (Zr0.6Sn0.33Ti0.07) O3 thin film - Correia, T. M.; Zhang, Qi (American Institute of Physics (AIP), 2010)
The permittivity maximum of a sol-gel derived Pb0.87Ba0.1La0.02 (Zr0.6Sn0.33Ti0.07) O3 (PBLZST) thin film was observed to appear at Tm=70 ºC rather than at 40 ºC as observed in the bulk ceramics with the same composition. Measurements of permittivity vs. electric field (E) present two maximums at 60 (polarizing) and 25 kVcm-1 (depolarizing), corresponding to antiferroelectric- ferroelectric and ferroelectric-antiferroelectric phase transitions, respectively. Calculations of tunability and Figure-of-Merit (FOM) display a maximum value of 75% at E = 350 kV cm-1 and ~ 141, respectively. These high tunable dielectric responses imply that PBLZST thin films can be an attractive material for tunable device application